Creep Behaviour of Near-Equiatomic Nickel-Titanium Wires - Eker, Aysegul Akdogan; Sonmez, Deniz; Kucukyildirim, Bedri Onur (CARL HANSER VERLAG, 2013)
The creep behaviour of near-equiatomic (50.8 at.-% Ni) NiTi wire with a diameter of 0.49 mm is studied between 82 MPa and 127 MPa tensile stress as well as in a temperature range of 575 degrees C to 650 degrees C. For 600 degrees C and between 82-107 MPa a stress exponent of n = 4.5 as well as for 82 MPa between 600-625 degrees C an activation energy of Q = 300 kJ mol(-1) have been found, these results have been compared with previous creep studies. In contrast to previous studies, this investigation has been performed with high stresses for thin NiTi wires. Moreover, fracture surfaces and ductility of wires have been investigated. The main reasons for the various results are discussed.
Keywords: SHAPE-MEMORY ALLOYS; HIGH-STRENGTH; NITI; Materials Science